Investigation of electrical and electric energy storage properties of La -doped Na0.3 Sr0.4Bi0.3TiO3 based Pb-free ceramics. Issue 11 (1st August 2020) - Liu, Gang; Hu, Lu; Wang, Yifei; Wang, Ziyang; Yu, Linjiang; Lv, Jingwen; Dong, Jia; Wang, Ying; Tang, Mingyang; Guo, Biao; Yu, Kun; Yan, Yan
Abstract: Na0.3 Sr0.4 Bi0.3 TiO3 with various concentrations in La modified ceramic specimens were fabricated using a traditional die-press process. All the obtained NBT-ST- x La ceramics exhibited a typical perovskite structure with a single phase, and the grain sizes were found to be uniform and fine. The electric breakdown strength of the sample after La doping increased significantly. In particular, the ceramic electric breakdown strength of x  = 0.02 component reached 190 kV/cm, the stored energy density reached 1.67 J/cm 3, and the efficiency was stable and greater than 80%. In addition, the ceramic with x  = 0.02 La also exhibited an excellent temperature, frequency stability, and good fatigue resistance. More specific and detailed analysis were conducted in this study.